1978
DOI: 10.2307/767348
|View full text |Cite
|
Sign up to set email alerts
|

Javanese Pélog Tunings Reconsidered

Abstract: The fixed pitch instruments of Java are justly famous for the flexibility of their tuning. The absolute pitches of various ensembles differ substantially, and within an ensemble, tones of a given name vary greatly in pitch when produced on different instruments. Causes for these differences include the gradual changes which occur in the metals used in the instruments’ manufacture, and the high value placed on the production of acoustical beats among the instruments of a single ensemble (Kunst 1973:251; Hood 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Consider the Gamelan pelog scale, variations of which account for over two thirds of cluster p. Pelog scales rarely contain imperfect fifths. A crude approximation of the pelog scale reduces it to intervals on a 9-tet scale (61). This scale is composed of 5 small intervals (average size 133 cents) and 2 large intervals (average size 267 cents).…”
Section: Discussionmentioning
confidence: 99%
“…Consider the Gamelan pelog scale, variations of which account for over two thirds of cluster p. Pelog scales rarely contain imperfect fifths. A crude approximation of the pelog scale reduces it to intervals on a 9-tet scale (61). This scale is composed of 5 small intervals (average size 133 cents) and 2 large intervals (average size 267 cents).…”
Section: Discussionmentioning
confidence: 99%
“…We wonder whether this societal difference would persist if we were to only compare measured scales from societies, since theory scales will certainly exhibit intonation variability when performed. In the literature, Western scholars often discuss variation in intonation in societies that lack mathematical musical theory as being an intentional form of expression [64,68,[138][139][140][141], whereas studies of classical musics typically investigate to which theoretical tuning system the musicians conform [13,123,126,127]. Ultimately, it is difficult to intuit the differences between societies, since there are only a few cross-cultural studies of interval discrimination [142,143].…”
Section: Plos Onementioning
confidence: 99%
“…Sugree et al (1997) reported fundamental-frequency measurements for 35 “bands,” that is, instrumental ensembles. Like Somchai (1973), theirs is one of the most extensive studies of tuning for Thai classical music, comparable in its scope to the path-breaking account of Central Javanese tuning by Surjodiningrat, Sudarjana, and Susanto (1972) that has been a basis for several further studies: for example, Dowling (1978), Rahn (1978), Carterette and Kendall (1994), Braun (2002), Sethares (2005), and Rahn (2016).…”
Section: Measurements Included In the Present Studymentioning
confidence: 99%